PERANCANGAN SISTEM PAKAR DIAGNOSA PENYAKIT EPILEPSI (STUDI KASUS RUMAH SAKIT RADEN MATTAHER) BERBASIS WEB: Expert Systems;Epilepsy;Forward Chainning;Web. - Susanto, Darex; Tamrin Syah (JURNAL AKADEMIKA, 2022)
The diagnosis of the disease made by an expert has its weaknesses as well as its biological weaknesses. One potential solution is an expert system. An expert system is a system that seeks to bring human knowledge into a computer so that it can solve problems as professionals are accustomed to. By trying to build an expert system for the diagnosis and treatment of epilepsy. There are 8 types of epilepsy, with a total of 92 symptoms. The inference method used is forward chaining. This method was chosen to overcome the problem of determining the type of disease by knowing the symptoms experienced. Web-based expert systems for easy system deployment. System performance is provided in consultation with answering questions posed by the system. This test gives patients what type of epilepsy they suffer from, so we can conclude that this system can be applied.